Analysis of the Effect of Perceived Security, Information Quality, and Consumer Trust on Online Purchase Intention in the Shopee Application (JEM17: Jurnal Ekonomi Manajemen, 2023)
The purpose of this study was to analyse the effect of perceived safety, information quality, and consumer trust on online purchase intentions in the Shopee application. This study uses quantitative research with a survey type of research. This study uses an online questionnaire as a data collection tool. The population of this study are users and have made purchases of e-commerce fashion in the Shopee application. The sampling technique was purposive sampling. The sample of this study was 170 respondents. Data analysis This research technique uses the Partial Least (PLS) method with SMARTPLS software. The results of this study are Security and perceived information quality have a positive effect on trust. Security and quality of information have a positive effect on purchase intentions. Trust has a positive effect on purchase intentions. Trust can partially mediate the relationship between perceived security and purchase intentions. Trust can partially mediate the relationship between information quality and purchase intention